Evaluation of corrosion mitigation of SS904l using inhibitors with statistical and morphological analysis - Dinesh Kumar Vairavel; Sivasubramanian Mahadevan; Narayanan Selvapalam; Vairavel Madeshwaren (Mechanical Engineering for Society and Industry, 2025)
This study evaluates the corrosion resistance of SS904L stainless steel, a highly alloyed material known for its exceptional performance in acidic environments, to address the need for optimized corrosion mitigation strategies. Corrosion inhibitors were utilized to enhance the material's durability, with the weight loss method employed to assess corrosion under varying conditions of temperature and pressure. Experiments tested inhibitor concentrations ranging from 0–5 mg per 100 mL over exposure durations of 24, 48, and 72 hours. Statistical analyses using ANOVA and regression confirmed a significant improvement in corrosion resistance with appropriate inhibitor concentrations. The Kesternich test provided comparative insights into the corrosion rate, validating the inhibitors' efficacy under simulated harsh conditions. Morphological analyses via X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM) revealed the formation of protective layers on the metal surface, contributing to enhanced durability. These findings emphasize the critical role of corrosion inhibitors in extending the service life of SS904L and establish a relationship between inhibitor concentration, exposure time, and corrosion performance, paving the way for advanced corrosion mitigation strategies.